A Detailed Experimental and Theoretical Study into the Properties of C60 Dumbbell Junctions. Issue 22 (30th April 2013) - Gillemot, Katalin; Evangeli, Charalambos; Leary, Edmund; La Rosa, Andrea; González, M. Teresa; Filippone, Salvatore; Grace, Iain; Rubio‐Bollinger, Gabino; Ferrer, Jaime; Martín, Nazario; Lambert, Colin J.; Agraït, Nicolás
Abstract A combined experimental and theoretical investigation is carried out into the electrical transport across a fullerene dumbbell one‐molecule junction. The newly designed molecule comprises two C60s connected to a fluorene backbone via cyclopropyl groups. It is wired between gold electrodes under ambient conditions by pressing the tip of a scanning tunnelling microscope (STM) onto one of the C60 groups. The STM allows us to identify a single molecule before the junction is formed through imaging, which means unambiguously that only one molecule is wired. Once lifted, the same molecule could be wired many times as it was strongly fixed to the tip, and a high conductance state close to 10−2 G0 is found. The results also suggest that the relative conductance fluctuations are low as a result of the low mobility of the molecule. Theoretical analysis indicates that the molecule is connected directly to one electrode through the central fluorene, and that to bind it to the gold fully it has to be pushed through a layer of adsorbates naturally present in the experiment.